Analysis of Fiscal Policy, Informality, and Economic Growth Nexus in Nigeria - Okeke, Chiamaka Lucy; Orji, Anthony; Nwosu, Emmanuel; Anthony-Orji, Onyinye (Unisia, 2024)
This study investigates the impact of fiscal policy on the informal sector and economic growth in Nigeria. In this study, fiscal policy is unbundled into two distinctive categories: government spending and tax burden. The study adopted the ARDL model and bound cointegration test to ascertain whether there is evidence of long- or short-run equilibrium relationships among the core variables. The results show that government expenditure has a positive and significant effect on the size of Nigeria’s informal sector. In the long run, tax or tax burden has no significant effect on the size of the informal sector in Nigeria. This might be attributed to the fact that not a significant number of businesses is captured in the tax net. The results further show that fiscal policy, measured as total government expenditure, has no statistically significant effect on Nigeria’s economic growth in the short run. However, a change in the tax burden has a positive and statistically significant effect on Nigeria’s economic growth. The study recommends that the government implement market-friendly policies that would help integrate the informal economy with the formal economy to boost government tax revenue and enhance fiscal discipline.